Изменение лингвистического ландщафта городов России: ономастическая категоризацуия - Щербак, Антонина (Studia Rossica Posnaniensia, 2015)
The process of lexical-semantic change in modern Russian manifests itself in the modernization of the onomasticon of towns. The names of particular objects in towns convey different kinds of information, which reveal the preferences of “the person who gives a name” and which involves a search for a new, original name. Among such names are title names and onyms (for example, the shops “Pyaterochka” and “Don Zhuan” or the grand hotel “Europe”). The language of the modern Russian town shows that onomastic terminology is of foreign origin, which is testimony to the fact that the sphere of object naming in post-Soviet times is free from ideological control. The ontological essence of the Russian language’s onomastic system is reflected in people’s consciousness. To put it simply, the emergence of a new onomastic category and terms helps to create a new perception of the names of objects in towns in society’s consciousness.